Strategi Relasi antara Franchisor dan Franchisee pada Usaha Waralaba Chifry - Teguh, Monika; Santoso, Jeremy; Njotoharsojo, Sasha Kurnia (representamen, 2020)
Franchise is a business license from the franchisor to the franchisee. The franchise business industry continues to show an increasing trend every year. One of the food franchise businesses that has successfully developed and has outlets in various cities in Indonesia is ChiFry. ChiFry has been established since 2015 and now has 27 outlets throughout Indonesia. This study aims to determine the relationship strategy of the franchisor with the franchisee in the ChiFry food business, where ChiFry within 4 years succeeded in opening 25 franchise branches. The research is based on customer relations theory because the franchisee is a customer of the franchisor. This research uses a descriptive qualitative approach with the case study method. The results of this study indicate that all elements of the relationship strategy at ChiFry such as commitment, communication, trust, respect, mutual understanding, confidentiality, and mutual exchange work well, thus encouraging customer satisfaction. This research also shows that when the franchisor meets aspects of customer satisfaction such as quality perception, perceived value, and handling complaints, it will create loyalty from the franchisee. Loyalty is manifested in the form of not breaking the contract of cooperation with the franchisor.Keywords : Customer Relations, Franchise, Relationship Strategy, Customer Satisfaction, Customer Loyalty